2016
DOI: 10.1002/jcb.25600
|View full text |Cite
|
Sign up to set email alerts
|

Resistance to 3‐HTMC‐Induced Apoptosis Through Activation of PI3K/Akt, MEK/ERK, and p38/COX‐2/PGE2 Pathways in Human HT‐29 and HCT116 Colorectal Cancer Cells

Abstract: Increasing incidence and mortality of colorectal cancer brings the necessity to uncover new possibilities in its prevention and treatment. Chalcones have been identified as interesting compounds having chemopreventive and antitumor properties. In this study, we investigated the effects of the synthetic chalcone derivative 3-hydroxy-3',4,4',5'-tetra-methoxy-chalcone (3-HTMC) on proliferation, cell cycle distribution, apoptosis, and its mechanism of action in human colorectal HT-29 (COX-2 sufficient) and HCT116 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 39 publications
1
16
0
Order By: Relevance
“…Oxidative stress is an activator for triggering apoptosis [32]. SubG1 accumulation is one of the apoptosis indicators [33]. In the current study, EANT partly induces subG1 accumulation and increases the intensity of annexin V. These apoptosis events were suppressed by NAC pretreatment, suggesting that EANT induces apoptosis of breast cancer cells depending on oxidative stress.…”
Section: Discussionsupporting
confidence: 52%
“…Oxidative stress is an activator for triggering apoptosis [32]. SubG1 accumulation is one of the apoptosis indicators [33]. In the current study, EANT partly induces subG1 accumulation and increases the intensity of annexin V. These apoptosis events were suppressed by NAC pretreatment, suggesting that EANT induces apoptosis of breast cancer cells depending on oxidative stress.…”
Section: Discussionsupporting
confidence: 52%
“…[33][34][35] ERK is an important factor for regulating proliferation, apoptosis, migration and invasion through various signalling in CRC cells. [36][37][38][39] Our findings demonstrated that overexpression of SPNS2 increased Akt and ERK phosphorylation and SPNS2-induced malignant behaviours were abolished by Akt or ERK inhibitor, suggesting that SPNS2 may regulate the malignancy of CRC cells by activating Akt and ERK signalling.…”
Section: Discussionmentioning
confidence: 55%
“…This corresponds with previous reports of the invasion-and metastasis-promoting roles of CUL7 in liver carcinoma (15,16), which further indicated a close association between CUL7 and EC progression. The ERK signaling pathway is also considered an important factor in various types of cell behaviors, including proliferation, migration and drug resistance (19,20), and results from the present study indicated that CUL7 may promote EMT via the ERK-SNAI2 signaling pathway, which may suggest novel targets for the treatment of EC.…”
Section: Discussionmentioning
confidence: 59%